2020
DOI: 10.3389/fpsyt.2019.01028
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Interoception and Emotion Regulation in Individuals With Alcohol Use Disorder

Abstract: Introduction: Sensing body-related information includes interoceptive sensibility (the tendency to focus on internal body sensations) and accuracy (precision in perceiving real internal processes). Interoception and emotion regulation have both been linked to alcohol use disorder (AUD). However, the association between these factors have not been investigated within a clinical group of individuals with AUD. Objectives: The current study examines associations between emotion regulation and interoceptive accurac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 61 publications
1
12
0
3
Order By: Relevance
“…Using this task, recently abstinent iAUD exhibit lower IA than healthy controls (CTL), with lower IA linked to greater self-reported alcohol craving [ 31 ]. Jakubczyk and colleagues [ 32 ] replicated and extended this finding, showing that iAUD have both lower IA and higher emotional dysregulation (measured by self-report) than CTL. Furthermore, lower IA in iAUD was associated with poorer self-reported ability to accept emotional distress.…”
Section: The Role Of Interoception In Sudmentioning
confidence: 85%
See 1 more Smart Citation
“…Using this task, recently abstinent iAUD exhibit lower IA than healthy controls (CTL), with lower IA linked to greater self-reported alcohol craving [ 31 ]. Jakubczyk and colleagues [ 32 ] replicated and extended this finding, showing that iAUD have both lower IA and higher emotional dysregulation (measured by self-report) than CTL. Furthermore, lower IA in iAUD was associated with poorer self-reported ability to accept emotional distress.…”
Section: The Role Of Interoception In Sudmentioning
confidence: 85%
“…Within iAUD, poor awareness or ability to identify emotional states has been identified as a risk factor for future alcohol use; it is argued that as these individuals are unable to accurately identify their emotional experiences and cope effectively, they instead turn to alcohol for relief from bodily sensations [ 33 ]. This finding suggests that improving IA and, therefore, one’s ability to identify and describe somatic states, may reduce risk of using alcohol consumption as a coping mechanism [ 32 ].…”
Section: The Role Of Interoception In Sudmentioning
confidence: 99%
“…Based on previous crises, some authors have suggested that the main mechanism that affects the increase in alcohol consumption is the increase in stress levels, promoted by the economic difficulties, social isolation, and uncertainty about the future ( de Goeij et al, 2015 ; Rehm et al, 2017 )After the SARS crisis of 2003, in a group of 800 Hong Kong residents who were regular drinkers, 4.7% of the men and 14.8% of the women reported an increase in alcohol consumption after 1 year ( Lau, Kim, & Tsui, 2005 ). Research should consider this population's capacity for self-regulation and self-awareness, because individuals with AUD who are more interoceptively sensitive may have problems controlling their behaviors while experiencing negative emotional states ( Jakubczyk et al, 2020 ). In our case, the number of first visits motivated by an increased consumption of drugs during the confinement was very similar in the two periods considered in our study: most of the cases were transferred from the emergency department and from different mental health care teams after being discharged from the short-stay unit of the hospital.…”
Section: Discussionmentioning
confidence: 99%
“…Further evidence of an impaired association between HEP amplitudes and heartbeat perception accuracy in depressive patients suggested the imbalance of allostasis in MDD ( 34 ). In addition, many researchers had reported the relationship between emotional information processing and interoception in psychiatric disorders, such as anxiety ( 35 ), alcohol use disorder ( 36 ), and functional neurological symptom disorder ( 37 ). However, previous research studies on interoception mainly focused on somatic symptoms in MDD ( 27 , 38 ).…”
Section: Introductionmentioning
confidence: 99%